Effect of Community Participation and Government Internal Control System on Village Government Fund Management with Organizational Commitment as Moderating Variable - Dede Yusuf Ansori; Swidia Caroline Dwitami (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze effect of community participation and government internal control system on village government fund management with organizational commitment as moderating variable. The design of this study used a descriptive survey method with expalanatory techniques. The population in this study is the Village Government in Sukabumi Regency, the northern region which consists of 168 villages located in 21 sub-districts. So that the villages that will be the sample in this study amounted to 50 villages with a total of 200 respondents. Of these, there are 12 non-returnable questionnaires and 188 returned questionnaires and 3 questionnaires that could not be processed, so the number of questionnaires that could be processed is 185 questionnaires. Testing and data analysis using multiple linear regression analysis and moderation test. The results show that community participation and government internal control system have a positive and significant effect on village government fund management in Sukabumi Regency. Organizational commitment is able to moderate effect of community participation on village government fund management in Sukabumi Regency. Organizational commitment is not able to moderate effect of government internal control system on village government fund management in Sukabumi Regency.